Abnormal relationship between Ms temperature and prior austenite grain size in Al-alloyed steels. (June 2017) - Zhu, Kangying; Magar, Coralie; Huang, M.X.
Abstract: It has been generally accepted in the literature that the decrease in prior austenite grain size leads to a decrease in Ms temperature in steels. However, in the present study, it is found that Ms temperature increases with the decrease of prior austenite grain size in steels with an addition of Al content higher than 1 wt%. It is revealed that the Al segregation at prior austenite grain boundaries may be the origin of this abnormal phenomenon. Graphical abstract: